Acute Cor Pulmonale - Regina, Anastasia Aura; Anisa, Anisa; Maharani, Annisa Dwi; Ramadhan, Ariq Naufal (Journal of World Future Medicine, Health and Nursing, 2023)
In physiological conditions the left heart ventricle produces a higher pressure which aims to pump blood throughout the body while the right heart ventricle has a lower pressure to pump blood to the lungs. If pulmonary hypertension or increased blood pressure in the pulmonary arteries occurs, it can cause the right ventricle of the heart to work harder to pump blood against the high pressure. If there is pulmonary hypertension in the long term so that the right ventricle of the heart is burdened, it will cause cor pulmonale. Cor pulmonale is hypertrophy or dilatation of the right ventricle caused by pulmonary hypertension. Pulmonary hypertension is caused by diseases that attack the structure, function of the lungs or pulmonary blood vessels that can progress to right heart failure. Cor pulmonale can be acute or chronic. This literature review in made to know the theoretical concept of patients with cor pulmonale disorders including definitions, epidemiology, pathophysiology, clinical features, interventions, and prognosis and complications in acute cor pulmonale patients.